Mapeamento e avaliação do grau de risco de inundação em áreas urbanas - Ferreira, Maurício Tolstoi dos Santos (2019)
Brazilian urbanization occurred in a differentiated way, in this perspective the most attractive places were being occupied by the real estate market, while the population with less purchasing power was forced to occupy marginal areas of cities, because they are economically attractive, but quite dangerous. These areas often had a precarious infrastructure, usually close to slopes, streams or river banks, in the wettest periods the resident population of these localities are vulnerable to events of extreme character, among them worth citing landslides, floods or floods. In the state of Rio Grande do Norte, floods are the second largest type of recurring disaster, from 1991 to 2010 this type of occurrence reached 20%, second only to the droughts totaling 80%. The most affected region of the state by floods is the sugar valley, which houses activities such as carciniculture, livestock and irrigated fruit growing. This region comprises the Piranhas-açu River basin, this river being the main supplier of water in the development of the sugar valley and its activities, in periods of water surplus the river overflowed, causing a series of socioeconomic disorders, in the years 2008 to 2009, were the last to have a flood record. In view of all this, we selected three municipalities of the sugar valley (Alto do Rodrigues, Pending and Carnaubais) both with a flood history, to evaluate what impacts such events would have, as well as the similarities and differences between the municipalities. We use a methodology that encompasses the construction of emergency flood maps combining with the vulnerability index, for the definition of a final risk map. Three years (1988; 2005 and 1985) were selected for the construction of the Emergency Flood Map, successively the normal, rainy and very rainy years, according to quantis frequency delimitation: Normal (0.35<q≤0.65), Rainy (0.65<q≤0.85) and Very Rainy (q>0.85) (XAVIER, 1999). Flood maps exhibited a variability in the water slide, which shows periods where water is limited to the smaller bed in normal periods, while in the wettest periods the water fills the entire floodplain. For the vulnerability maps, this cartography was conventionally used as a territorial unit, the census tracts of IBGE and through the methodology developed by Brito (2017), possession of several socioeconomic variables, this cartography was constructed, which after completion, showed vulnerability very concentrated in urban areas, we overlapthis result with the flood threat map, and the final result was the risk map, which demonstrated three urban spots that project the differentiated form of risk, basically Alto do Rodrigues presented higher risk followed by Backlogs and Carnaubais, the latter with the lowest risk of flooding, linked to its urban spot.